2008
DOI: 10.2323/jgam.54.385
|View full text |Cite
|
Sign up to set email alerts
|

A cold-active extracellular metalloprotease from Curtobacterium luteum (MTCC 7529): Enzyme production and characterization

Abstract: A novel psychro-tolerant bacterium, Curtobacterium luteum, secreting an extracellular protease was isolated from the soil of Gangotri glacier, Western Himalaya. Maximum enzyme production was achieved when the strain was grown in a pH-neutral medium containing skim milk at 15 C over 120 h. The metal ions such as Zn 2+ and Cr 2+ enhanced enzyme production. The specifi c activity of purifi ed enzyme was 8,090 units/mg after 34.1-fold purifi cation. The 115 kDa enzyme was a metalloprotease (activity inhibited by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…The data obtained indicated that there was strong influence of pH on enzyme production. The pH of medium strongly affects many enzymatic processes and transport of compounds across the cell membrane [23]. Lipase production declined on either side of the optimum pH and was minimal at pH of 10.…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained indicated that there was strong influence of pH on enzyme production. The pH of medium strongly affects many enzymatic processes and transport of compounds across the cell membrane [23]. Lipase production declined on either side of the optimum pH and was minimal at pH of 10.…”
Section: Resultsmentioning
confidence: 99%
“…from Antarctic region [36], Colwellia sp. from sea ice [37] and sub-antarctic sediments [38], Curtobacterium luteum from glacier soil [39], Exiguobacterium sp. from cold desert soil [40], Pedobacter cryoconitis from glacier ice [41], Penicillium chrysogenum from cold marine environment [42], Pseudomonas sp.…”
Section: Microbes Producing Cold-active Proteasesmentioning
confidence: 99%
“…This specific property of cold-active enzymes make them valuable in industry and research due to their less requirements, reduced process times, save energy costs, easy inactivation by mild heat, and the loss of volatile compounds [18,39]. However, in the field of food biotechnology, it needed extra effort to cope various bottlenecks specifically high cost of enzyme isolation and purification, low stability of most cold-active enzymes and least explored cold-adapted microbes from the cold habitats.…”
Section: Future Prospectsmentioning
confidence: 99%